A case of primary cervical lymphoma in a patient with abnormal uterine bleeding - Maureen E. Roberts; Hope M. Cottrill (Elsevier, 2018)
Primary lymphoma of the uterine cervix is a rare site of extranodal lymphoma. Many gynecologic oncologists may go their entire career without encountering one. Patients may present with symptoms of abnormal or postmenopausal bleeding, and diagnosis may be challenging as typical office tests such as the pap smear may not detect the abnormal cells. Once a diagnosis is made, management may be debated due to the rarity of the condition and lack of accepted standard treatment. However, most patients respond well to some version of chemotherapy and radiation typically used for standard lymphomas. Prognosis is favorable if the patient is diagnosed early in the disease process. Keywords: Extranodal lymphoma, Papanicolaou test, Chemotherapy, Radiation, Hysterectomy